Chemogenomics - Overington, John P. (Henry Stewart Talks, 2012)
Drug discovery, Ligand binding, SAR table, Correlation of binding, Binding site, Binding features mapped, Clinical candidates, ChEMBL, Drug optimisation, Compound searching, Different data views, Drug target assessment, Different scoring types